Bone turnover and trabecular plate survival after artificial menopause. - Reeve, J (1987)
Considerable bone loss often occurs after menopause, particularly if menopause is induced by surgery. For perhaps two years bone formation fails to keep pace with the rapid acceleration of bone resorption that occurs after sex hormone withdrawal. The threat that this poses to the integrity of the skeleton is not clear. Because ethical constraints limit histological studies in normal women existing normal data and statistical modelling techniques were used to explore the dynamics of iliac trabecular bone after menopause. Trabeculae are breached during remodelling when the osteoclasts resorb to a depth equal to the trabecular thickness. Since holes in trabecular plates cannot normally be bridged such defects are probably permanent. Men lose 7% of their vertebral trabecular bone every 10 years; deeper than average resorption of trabeculae at the thin end of the normal range would account for it. The dramatic losses of trabecular bone that are seen in some postmenopausal women, however, require a period of imbalance between bone formation and bone resorption since this leads rapidly to generalised thinning. The statistical model suggested that an imbalance lasting only two years may account for eventual losses of up to half of the iliac trabecular bone. Further understanding is needed of what determines the amount of bone lost in the immediate postmenopause, which varies considerably among women. A simple mean is needed of identifying women who will lose bone most rapidly at the menopause. This must be suitable for use in general practice because these women should probably be offered long term hormone replacement treatment within a few months of the last menstruation.